Application of diffusive gradient in thin films (DGT) technique for heavy metals monitoring in water system (case study Lam River, Nghe An, Viet Nam) - Nguyen Duy Hung (College of Engineering, University of the Philippines Diliman, 2012)
This study aims to investigate the application of Diffusive Gradient in Thin Films (DGT) as a passive sampling method to monitor heavy metals f mercury (Hg. Copper (Cu), lead (Pb) cadmium (Cd) and Zn (zinc) in water systems. In laboratory works, the uptake of heavy metals to DGT device shows as a function of time and follows two main regimes: a fast adsorption in which the transfer rate of metals from solution phase to receiving phase of DGT devices was increasing with respect to time, and a slow accumulation in which a thermodynamic equilibrium was established between the two phases after only seven (7) days. Result also shows that different metals require various periods of time to reach the equilibrium. Lam river basin (Viet Nam) was chosen to verify DGT capabilities in field applications. Likewise, metal speciation assessment was made for Lam river basin by combining DGT and bottle sampling techniques. Results indicate that free and labile fractions of Cd and Zn are considered the major constituents while those fractions of Cu, Pb and Hg are in minor contents compared to their total contents compared to their total contents in the environment. It also shows that the free and labile species of the five metals vary with respect to time in field applications. An assessment of water quality of Lam river basin shows that is contaminated with Hg and Cu with pollution increasing from upstream to downstream parts of the river. This is attributed to the presence of gold mining activities, which have been going on for years, and are considered as one of the major sources of contaminations upstream. An overall water quality monitoring system comprising of thirty reference-monitoring stations is then proposed as strategic sites to impose control and eventually results in protection and conservation of the basin where DGT is a potential passive sampler to regularly monitor heavy metals along the basin.